التعلم القائم على الموقع الإلكتروني باستخدام تطبيق Blogger - Shofil Fikri; Alya Afifah Maliyanah; Sri Hardianti Rukmana (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2024)
Web-based learning is an educational activity using media websites that can be accessed via the Internet. Web-based learning is one of the types of electronic learning applications (E-Learning). The purpose of this research is to identify On learning techniques and tools on the Internet and their applications in learning the Arabic language. This research is a qualitative descriptive research using desk study by reading books, magazines, etc. The results of this study are that there are several types of educational media based on websites, as follows: edmodo and schoology And moodle and google classroom. The researcher focuses on educational media using websites through the Blogger application, and teachers can easily use websites and build an online learning environment. The researcher will describe the steps to create a website through Blogger.